Influences of the mole ratio SnO2/NaOH on the growth of SnO2 nanorods - Trung, Khuc Quang; Hien, Vu Xuan; Vuong, Dang Duc; Chien, Nguyen Duc (Vietnam Journal of Chemistry, 2014)
SnO2 nanorods have been successfully prepared by hydrothermal method at low temperature. The mole ratio of SnO2/ NaOH plays important role in the morphology and diameter of SnO2 nanorod. Besides, the possible growth mechanisms of SnO2 nanorods are also discussed. Structural properties and surface morphologies of the SnO2 nanorods were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The experimental results show that diameters of the nanorods are around 100 nm to 300 nm with lengths of several micrometers. With the success of preparing SnO2 nanorods, which will improve in the research and preparation of gas sensor based on SnO2 materials. Keywords: SnO2, nanorods, hydrothermal method.